A bibliometric review and the direction of future vegan-related research: a qualitative approach - Hong, Chuan Loh; Kwan, Jia Ni; Lim, Yi Fang; Hoo, Fan Kee; Looi, Irene (The Plantrician Project, 2022)
Veganism, a lifestyle that encourages healthy and sustainable living, is gaining more attention. The rising demand for sustainable ways of living has stimulated research initiatives globally. We sought to comprehend the topics of interest to researchers and took a qualitative approach in examining vegan-related research trends worldwide. This article aims to provide a synthesis of underlying research themes and identify the direction of future vegan-related research. We selected relevant articles published between 1960 and 2020 from the Scopus database and performed a bibliographic coupling analysis with the open-source R programming software-based Bibliometrix package followed by a content analysis. We identified four main clusters and the associated sub-clusters for each of them: a) consumerism (cultural, social, personal, and psychological factors), b) medical and health sciences (nutrition, biomarkers, anthropometry, fat and/or cholesterol, blood glucose, gut health, blood pressure, general health, ageing and/or quality of life, physical or exercise performance, mortality or longevity, bone health, and genetics), c) food science and technology (vegan food products or by-products, vegan vitamins or supplements, and vegan food content or toxic elements), and d) environmental impacts (greenhouse gas emissions, land and water use). Our study provides a wide-ranging overview of research domains and introduces readers to key studies, concepts, and methods. These are essential to help researchers conduct more studies for effective policy prescriptions